Overcoming Multidrug Resistance in Bacteria Through Antibiotics Delivery in Surface-Engineered Nano-Cargos: Recent Developments for Future Nano-Antibiotics - Yang, Xinfu; Ye, Wenxin; Qi, Yajun; Ying, Yin; Xia, Zhongni (Frontiers in Bioengineering and Biotechnology, 2021)
In the recent few decades, the increase in multidrug-resistant (MDR) bacteria has reached an alarming rate and caused serious health problems. The incidence of infections due to MDR bacteria has been accompanied by morbidity and mortality; therefore, tackling bacterial resistance has become an urgent and unmet challenge to be properly addressed. The field of nanomedicine has the potential to design and develop efficient antimicrobials for MDR bacteria using its innovative and alternative approaches. The uniquely constructed nano-sized antimicrobials have a predominance over traditional antibiotics because their small size helps them in better interaction with bacterial cells. Moreover, surface engineering of nanocarriers offers significant advantages of targeting and modulating various resistance mechanisms, thus owe superior qualities for overcoming bacterial resistance. This review covers different mechanisms of antibiotic resistance, application of nanocarrier systems in drug delivery, functionalization of nanocarriers, application of functionalized nanocarriers for overcoming bacterial resistance, possible limitations of nanocarrier-based approach for antibacterial delivery, and future of surface-functionalized antimicrobial delivery systems.